Pengaruh Konsentrasi Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Tanaman Bawang Daun (Allium fistulosum L.) pada Tanah Ultisol - Ya'kub; Bakti Nur Ismuhajaroh; M. Laily Qadry Sukmana (AgroGreen, 2026)
The study aimed to determine the effect of Jakaba Liquid Organic Fertilizer (POC Jakaba) application on the growth and yield of leek (Allium fistulosum L.) on Ultisol soil and to determine the optimal POC Jakaba concentration for the growth and yield of the leek plants. The research was conducted at the Greenhouse of SMK-PP Negeri Banjarbaru and the Agricultural Biology Laboratory, Agronomy Department, Faculty of Agriculture, Lambung Mangkurat University, from November 2024 to June 2025. The research design used was a Single Factor Completely Randomized Design (CRD) with seven levels of POC Jakaba concentration: k₀ = 0 mL L⁻¹, k₁ = 20 mL L⁻¹, k₂ = 40 mL L⁻¹, k₃ = 60 mL L⁻¹, k₄ = 80 mL L⁻¹, k₅ = 100 mL L⁻¹, and k₆ = 120 mL L⁻¹, each replicated four times, resulting in 28 experimental units. Observed parameters included plant height (cm), stem diameter (mm), number of leaves per clump (leaves), percentage of tillers (%), root volume (cm³), fresh weight per clump (g), dry weight per clump (g), and productivity (ton ha⁻¹). The results of this study indicate that Jakaba POC significantly affected the number of leaves at 10 days after planting. The highest number of leaves (2.67 leaves) was produced at a Jakaba POC concentration of 20 mL L-1, which was significantly different from the k₆ treatment (120 mL L⁻¹) by 2 leaves.